Micosis en el Hospital Universitario del Valle (Colombia Medica, 1981)
The present study reviews the incidence and diagnosis of various mycotic diseases during eleven years (1968-1979) of the Micology Laboratory of the Hospital Universitario del Valle (HUV). Data shown reveal the importance of  mycological diagnosis. The need for training centers so that well prepared personal be available for the early diagnosis of such diseases, which constitute a serious problem in some areas of Colombia, is stressed.